Study of the effect of operating condition changes on the performance of photovoltaic cells - BEN ALI ABDELKADER; AGUIEB YAHIA; CHOUIRFAT TAHER (University of Shahid Hama Lakhdar - El Oued, 2025)
This thesis investigates the impact of operational condition changes on the performance of photovoltaic (PV) cells. It analyzes several environmental factors such as temperature, solar irradiance, dust, shadow, humidity, and natural degradation. The study shows that these conditions significantly influence the efficiency and electrical output of solar cells. An experimental setup using a real-time I-V data extraction system with a Buck-Boost converter and AI-based diagnostics was applied. The findings highlight the importance of regular maintenance, precise monitoring, and advanced fault-detection strategies to ensure better reliability and energy yield from PV systems under diverse conditions تبحث هذه الأطروحة في تأثير تغيرات الظروف التشغيلية على أداء الخلايا الكهروضوئية. وتُحلل الدراسة عدة عوامل بيئية، مثل درجة الحرارة، والإشعاع الشمسي، والغبار، والظل، والرطوبة، والتدهور الطبيعي. وتُظهر الدراسة أن هذه الظروف تؤثر بشكل كبير على كفاءة الخلايا الشمسية وإنتاجها الكهربائي. وقد طُبقت تجربة باستخدام نظام استخراج بيانات الجهد الكهربي الفوري (I-V) مع محول باك-بوست (Buck-Boost) وتشخيصات قائمة على الذكاء الاصطناعي. وتُبرز النتائج أهمية الصيانة الدورية، والمراقبة الدقيقة، واستراتيجيات الكشف المتقدمة عن الأعطال لضمان موثوقية أفضل وإنتاجية طاقة أفضل من أنظمة الخلايا الكهروضوئية في ظل ظروف متنوعة.
Master's thesis in electromechanics.2025
Keywords: Photovoltaic cells; solar irradiance; temperature; dust; shading; humidity; degradation; efficiency; Buck-Boost converter; maximum power point tracking; انخلايب انكهشوضىئيت; الإشؼبع انش سًي; دسخت انحشاسة; انغببس; انظم; انشطىبت; انخذهىس; انكفبءة; يحىل حخبغ قَطت انقذسة انقصىي.; Boost